Syariat Islam dan Kemaslahatan Manusia di Era New Normal pada Kegiataan Keagamaan dan Pendidikan - Mukran H. Usman; Aswar Aswar; Andi Wahyu Irawan (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2020)
Shari'a is a rule or law that is sourced from Allah Ta'ala to be a guide to human life so that it impacts on the benefit of life, both personally and socially. The Shari'a of Allah Ta'ala, everything is benefit and there is no evil, although sometimes it is considered bad by humans, but in essence is good for humans themselves. This study aims to explore the harmony of Islamic law on the benefit of humans in the midst of the Covid-19 outbreak. The details are aimed at giving explanations and religious insights that are washatiyah (moderate) from a number of suggestions in the form of a prohibition or restriction by the government regarding religious activities and education carried out face to face when the Covid-19 outbreak occurred. The research method used is the library research method with a phenomenological and normative approach. The issues studied are sourced from literacy which has a relation to the focus of the research, obtained from reading turats, research results and others. The results showed that the government's prohibition on termination and restriction in religious and educational activities during the Covid-19 period, such as: restrictions on religious and educational activities carried out face-to-face, were cases permitted in the Shari'a for human benefit.